The influence of cooling rates on microstructure and mechanical properties of Bi1,6Pb0,4Sr2Ca2Cu3Oysuperconductors - Çetinkara, Hacı Ali; Yılmazlar, Mustafa; Öztürk, Özgür; Nursoy, Mustafa; Terzioğlu, Cabir (IOP Publishing, 2009)
We investigated the effect of cooling rates on the microstructure and mechanical properties of Bi1,6Pb0,4Sr2Ca2Cu3Oy superconductors prepared by standard solid state reaction methods. The samples were annealed under identical condition and cooled with different cooling rates. The investigations consisted of Vickers microhardness, SEM and XRD measurements. XRD examination of the samples showed that high percentage of Bi-2212 phase was observed and low-Tc phase increased with increasing the cooling rates. From SEM analysis, flake-like grains were more pronounced with increasing cooling rates. The indentation load versus diagonal length of the samples under different indentation loads in the range of 0.245-2.940 N were presented. We calculated Vickers hardness, Young's modulus, yield strength, fracture toughness values. These mechanical properties of the samples were found to be load and cooling rate dependent. In addition, we calculated the load independent microhardness, Young's modulus, and yield strength and fracture toughness of the samples using different models. The possible reasons for the observed changes in microstructure and mechanical properties of the samples due to cooling rates were discussed.
Keywords: Superconductors; Mechanical; Microstructure